Flora and vegetation of the municipality of Álamo Temapache, Veracruz, Mexico - Francisco-de la Cruz, Axel; Villarreal-Quintanilla, José A.; Estrada-Castillón, A. Eduardo; Jasso-Cantú, Diana (Instituto de Ecología, A.C., 2017)
Background and Aims: The aim of this study was to know the flora and to describe the vegetation of the municipality of Álamo Temapache, Veracruz. The area is located in the north of this state and covers 1280.62 km2.Methods: A delimitation of the area was realized and collection routes for recognition of vegetation types were determined. Data of the vegetation types and components were taken and botanical samples collected. Finally, a vegetation map was made and a list of habit, common name and vegetation type for each species was elaborated.Key results: The results show a floristic list of 753 species, 491 genera and 124 families. The families with highest species numbers are Fabaceae, Asteraceae, Poaceae and Malvaceae. Eight vegetation types are recognized for the area: tropical evergreen forest, tropical deciduous forest, oak forest, palm forest, subaquatic and aquatic vegetation, secondary vegetation, weed community, and grassland. Most of the area is occupied by orchards and farmland. The weed community is the most extensive in the area, followed by induced grassland and tropical deciduous forest.Conclusions: The area has been radically changed by anthropic activities, only 8% of the original vegetation remains.